Association between goal-kick strategies and the offensive outcome in the UEFA Euro 2020 - Matheus Henrique de Amorim Mendes; Vitor Hugo Santos Rezende; Gibson Moreira Praça (Termedia Publishing House, 2023)
Purpose This study investigates the association between different goal kick strategies and the success of the offensive sequence in games of the Men's UEFA Euro 2020. The study hypothesis is that using the short pass as the goal kick strategy may generate more successful offensive sequences than the long pass strategy. Methods The data collection was accomplished by observing 595 goal kicks collected from 51 games of the referred competition. The analysed variables were the type of goal kick (short or long) and the result of the offensive sequence (successful and unsuccessful). These variables were collected through an observational instrument. The logistic regression and the association chi-square test were used to analyse the association between the type of goal kick and the offensive outcome. Results The results indicate significant associations between the variables 'type of goal kick' and 'result of offensive sequence' ( p = 0.021, z = 2.1). The regression analysis revealed that the model accurately predicts 64% of the offensive outcome based on the goal kick strategy. The short goal kick strategy was related to the unsuccessful offensive sequences, and the long goal kick strategy was associated with the successful offensive sequences. These results are contrary to the initial study hypothesis. Conclusions This study concludes that the long goal kick strategy showed more efficiency than the short goal kick strategy in obtaining possession of the ball in the offensive half.